Development of Relocation Strategies Regarding Eruption Hazard in Mount Merapi - Rosdiana Puji Lestari (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
The research was conducted to answer a questions: 1) how the relocation of the current strategy was carried out by the government 2) the problems that arise in the relocation which has yet to be resolved, 3) how the good concept of relocation so that these problems can be minimized. The research methodology used in this study combined quantitative and qualitative methods. Qualitative methods are used to explain the empirical facts that exist in each of these conditions in the relocation settlements. SWOT analysis is used to provide an overview of the strengths, weaknesses, opportunities and threats in the relocation of victims of Merapi. Information, facts and issues that arise in the study will be described, explained and analyzed primarily for the impact of residential relocation on social and economic life of the community. Relocation concept of the economic aspects of community empowerment efforts should be made related to community economic recovery after a change in livelihood. In addition, the potential of community mapping needs to be done by the government to be optimized and developed. From the aspect of government settlements seek to transfer ownership of land in the new settlement which may be the property of the citizens so that citizens obtain legal certainty while occupying the new settlement. The social aspects of the development potential of relocating residents and making it as a tourist village, residents need to support that relocation is no longer a newcomer, they have the same rights and obligations with citizens of another.